2010
DOI: 10.1111/j.1651-2227.2010.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of faecal calprotectin as a valuable non‐invasive marker in distinguishing gut pathogens in young children with acute gastroenteritis

Abstract: f-CP facilitates early discrimination between bacterial and viral causes of AG in young children. Combining f-CP with CRP increases the diagnostic power of diagnosing BAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 32 publications
2
46
1
4
Order By: Relevance
“…Weh et al [12] showed that C-Reactive Protein, serum Interferon gama, and the fecal proteins lactoferrin and f-CP might be useful in differentiating between bacterial and viral gastroenteritis in adults. Sykora et al published that f-CP facilitates early discrimination between bacterial and viral causes of AGE in children before the age 3 [13]. Similarly to this study, our study indicated that f-CP levels are significantly higher in patients with microscopy-positive groups in especially proven bacterial gastroenteritis, such as Salmonella and Shigella infections, but lower in patients with Rotavirus, Adenovirus, and Norovirus infections.…”
Section: Discussionsupporting
confidence: 81%
“…Weh et al [12] showed that C-Reactive Protein, serum Interferon gama, and the fecal proteins lactoferrin and f-CP might be useful in differentiating between bacterial and viral gastroenteritis in adults. Sykora et al published that f-CP facilitates early discrimination between bacterial and viral causes of AGE in children before the age 3 [13]. Similarly to this study, our study indicated that f-CP levels are significantly higher in patients with microscopy-positive groups in especially proven bacterial gastroenteritis, such as Salmonella and Shigella infections, but lower in patients with Rotavirus, Adenovirus, and Norovirus infections.…”
Section: Discussionsupporting
confidence: 81%
“…The f-CP level in C. concisus patients was significantly lower and 41 patients had normal f-CP (<50 mg/kg). This finding reflects the lower intestinal inflammation in these patients compared with C. jejuni/coli patients, and the f-CP levels in C. concisus infection could be compared with viral gastroenteritis although with a prolonged clinical outcome [5,9,10]. The authors conclude that clinicians should be aware of C. concisus infection, especially in patients with prolonged mild diarrhea, in the differential diagnosis to IBD.…”
mentioning
confidence: 74%
“…It is important to remember that all evidence indicates that a raised faecal calprotectin is indicative of organic disease but has no role in the differential diagnosis of the type of disease 9. Increased faecal calprotectin concentrations have been reported in bacterial gastroenteritis in adults10 and children,11 colorectal cancer12 and diverticular disease 13…”
Section: Calprotectinmentioning
confidence: 99%